THE ISLAMIC POLICY OF PORTUGUESE COLONIAL MOZAMBIQUE, 1960-1973 - Machaqueiro, Mário (2013)
Drawing its information from different documents in Portuguese and French archives, this article examines the evolution of Portuguese colonial policies regarding Islam, focusing the special case of Mozambique. Such policies evolved from an attitude of neglect and open repression, prevalent in the early years of the colonial war, when Muslims were perceived as main supporters of the anti-colonial guerrilla in northern Mozambique, to a more nuanced approach that tried to isolate ‘African Muslims’ from foreign influences in order to align them with the Portuguese combat against the anti-colonial movement. The article analyses the latter strategy, assessing its successes and failures and the contributions made by several actors that were engaged in this achievement: the Catholic Church, the core of political power and its local ramifications in the colonies.